Importance of the dentist and the auxiliary oral health team in the diagnosis of syphilis - Alexandre Cândido da Silva; Camila Correia dos Santos; Kelly Cristine Taquínio Marinho; Isabela Cândido Pollo; Élcio Magdalena Giovani (Editorial Ciencias Médicas, 2020)
Introduction: Syphilis is classified as a sexually transmitted infectious-contagious disease with the causative agent Treponema pallidum (Tp). It presents distinct stages of evolution: The primary phase is characterized by the appearance of the hard chancre, the secondary phase by the spread of Tp through the bloodstream and systemic involvement, and the tertiary phase by organ infection and nervous system impairment. In congenital syphilis, the Tp is transmitted vertically from mother to child. Objective: Report a case in which the dental team participated in the diagnosis of syphilis. Case presentation: A male 26-year-old patient with leukoderma, HIV-positive and under regular antiretroviral treatment, with no other chronic systemic changes and no previous history of Tp infection, was referred for evaluation by the oral health team. The patient reported having had bisexual relations in recent months with a condom and orogenital contact without a condom. He had not noticed any type of "wound" on the body. Intraoral examination found multiple reddish macules scattered on the lingual dorsum, with a slight detachment and little pain. The quick test was a reagent for syphilis. The patient was referred for evaluation at the medical clinic. Treatment started by two applications of benzyl penicillin with a 7 days' separation between them. Complementary blood tests were also indicated, with special attention to VDRL, which eventually confirmed the Tp infection. Conclusions: Participation of the oral health team in the diagnosis of syphilis constitutes a complementary force for the improvement of health care processes.